(untitled) (Can Tho, 2013)
This 174-page colored book presented systematically in both Vietnamese and English languages will be very helpful for education, research, practical activities of aquatic resources management. Through standard research methods, this importantly scientific work described 322 species belonging to 77 fish families collected in the Mekong Delta river basin for over 6 years of study from 2006 to now. As an output of the joint research project between Can Tho University, Viet Nam and NAGAO Environment Foundation, Japan, the research team including Dr Tran Dac Dinh, Dr Shibukawa Koichi, Assoc Prof. Dr. Nguyen Thanh Phuong, Dr Ha Phuoc Hung, Mr Tran Xuan Loi, Mr Mai Van Hieu, and Dr Utsugi Kenzo has prepared and published the book entitled “Fishes of the Mekong Delta, Viet Nam”.
Nguồn lợi thủy sinh vật,Phương pháp thu và phân tích số liệu nghề cá,Đánh giá và quản lý nguồn lợi thủy sản
Keywords: Biologicalc resources,Fisheries management,Quản lý nguồn cá